Insect anatomy : the curious world of bees, beetles, butterflies, and bugs - Rothman, Julia; Hearst, Michael, 1972- (Rothman, Julia. Anatomy series., 2025)
"Millions of species of insects fly, crawl, dig, swarm, and eat on every continent. Our very existence depends on them; without pollinators, we would have no food, and without decomposers, the world would be covered in decaying plant and animal material. With her signature style, Julia Rothman delves into this incredible world, uncovering amazing facts about bees, beetles, butterflies, and so much more"-- Provided by publisher.